Thinking Skills in the 12th Grade English Course book in Timor Leste - Hei, Joaninho Xavier (Beyond Words, 2017)
This study aims to analyze the English course book of (Manual do Aluno INGLÊS 12.o ano de escolaridade/Students’ English Manual for 12th Year Schooling) in Timor Leste. The activities in the reading and listening sections of the course book were performed to determine whether they emphasized on lower or higher levels of cognitive process. The study attempted to answer the following question: Do the cognitive levels of the activities that relate to the focus on reading and listening in the 12th grade English course book sufficiently represent all the six levels of the New Bloom Taxonomy of thinking skills? The objective of this analysis was to discover the reading and listening activities that can sufficiently promote the levels of cognitive process. The activities determined as the criteria for analysis were: Wh-questions, true/false question, yes/no question, multiple choice question, complete the sentence phrase, a chart, matching questions, statement question, and a key word request question. The activities of the questions were gathered, listed with the total numbers of 161 questions and analyzed according to the six levels of New Bloom’s Taxonomy. The results showed that 98 activities emphasized mostly on lower levels cognitive order while only 63 activities emphasized the higher levels of thinking skills. So, the course book mentioned above targeted as a resource for students to learn the language, not as a resource for students to develop thinking skills because it fails to equip learners with the activities requiring higher levels of thinking order. By implication, for the teacher/syllabus designer can be aware to modify their own learning material by integrating more higher-order questions to achieve higher levels of thinking skills. Keywords: Course book Activities Analysis, and New Bloom’s Taxonomy